Problematic social media use and phubbing: the mediating role of FoMO and urgency - Llamas Salguero, Fátima; Hidalgo-Fuentes, Sergio; Martínez-Álvarez, Isabel; González-Fernández, Alberto (Revista Complutense de Educación, 2026)
Phubbing, a behavior that involves ignoring people and one’s surroundings due to smartphone use, has generated growing interest because of its social and psychological implications. This study analyzes the relationship between problematic social media use and phubbing, exploring the mediating role of Fear of Missing Out (FoMO) and emotional urgency. The sample consisted of 591 university students selected through convenience sampling. Validated questionnaires, including the Short Social Network Addiction Scale and the Phubbing Scale, were administered via an online survey. Data were analyzed using parallel mediation models with the PROCESS macro for SPSS. The results show that problematic social media use significantly predicts both FoMO and urgency, which act as partial mediators in the relationship with phubbing. Furthermore, FoMO was found to have a greater mediating effect than urgency. These associations highlight the complexity of interactions between the variables. It is concluded that phubbing is not only linked to compulsive social media use but is also mediated by psychological factors. These findings underscore the importance of designing interventions aimed at reducing FoMO and impulsivity to mitigate the negative consequences of phubbing.
Keywords: phubbing; social media; smartphone; problematic social media use; university students